Promoting a Smiling Islam: Religious Moderation in the Virtual Da'wah of Habib Husein Ja'far - Ngainun Naim; Ahmad Yuzki Faridian Nawafi; Mustofa, Saiful; Diky Mohamad Fauzi (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University (UIN) Jakarta, 2025)
The emergence of new media has reshaped the landscape of Islamic da’wah in Indonesia, shifting religious authority from traditional institutions to digital platforms. This article seeks to discuss how Habib Husein Ja’far Al Hadar—one of Indonesia’s most influential millennial preachers (dai)—promotes a form of “Smiling Islam,” characterized by tolerance, inclusivity, and religious moderation, through his YouTube channel “Jeda Nulis.” Employing Social Network Analysis (SNA) and content analysis of twenty-one videos uploaded between 2019 and 2023, this article identifies four key indicators of religious moderation: tolerance, anti-violence, national commitment, and acceptance of tradition. Findings show that Husein Ja’far’s da’wah is dominated by messages of tolerance (82.4%) and non-violence (58.5%), supported by a millennial-friendly communication style, interfaith dialogues, and collaborations with influencers. The study also explores contestation surrounding his online presence, particularly accusations of Shia affiliation propagated by right-wing Islamic actors and conservative groups within Nahdlatul Ulama (NU). SNA of audience responses indicates that the majority of netizens reject these accusations, highlighting the role of media framing and communication distortion in shaping sectarian narratives. Overall, the research demonstrates that Habib Husein Ja’far’s digital da’wah not only challenges the dominance of conservative voices in Indonesia’s virtual religious sphere but also contributes significantly to mainstreaming religious moderation among young Muslims.